Field Trips Improve Student Understanding of Hindu-Buddhist Heritage: Kunjungan Lapangan Meningkatkan Pemahaman Siswa tentang Warisan Hindu-Buddha - Alfun Salam; Yuli Ifana Sari; Onik Farida Nikmatullah (Universitas Muhammadiyah Sidoarjo, 2025)
General background: Social Studies (IPS) learning on historical heritage often relies on lecture-based methods that limit student engagement and conceptual understanding. Specific background: At SMA Islam Sidoarjo, teaching Hindu–Buddhist heritage has not yet optimally utilized local sites such as Candi Tawangalun as contextual learning resources. Knowledge gap: Empirical evidence on the effectiveness of field trip (karyawisata) methods in improving senior high school students’ understanding of Hindu–Buddhist heritage remains limited. Aims: This study examines the influence of the field trip method to Candi Tawangalun on students’ understanding of Hindu–Buddhist heritage in grade X IPS. Results: Using a quasi-experimental pretest–posttest control group design (N = 100), the experimental classes showed significantly higher gains (N-Gain 0.57–0.58; moderate) than the control class (N-Gain 0.27; low), supported by strong observation and questionnaire scores. Novelty: The study integrates local temple heritage as a structured field-based IPS learning model at the SMA level, combining cognitive outcomes with students’ affective and motivational responses. Implications: Findings underscore the need for schools and teachers to institutionalize field trip–based, local-history learning to enhance understanding, engagement, and appreciation of cultural heritage in IPS instruction. Highlights: Shows that field trips to local temples significantly improve students’ understanding of Hindu–Buddhist heritage. Demonstrates higher learning gains in experimental classes compared to traditional lecture-based teaching. Highlights the importance of integrating local cultural sites into IPS learning to boost engagement and appreciation. Keywords: Hindu–buddhist Heritage, Field Trip Method, Social Studies Learning, Candi Tawangalun, Student Understanding